Cerebral Specialization for Speech and Complex Verbal Movements in Down Syndrome - Heath, Matthew (My University, 1997)
The neurobehavioural organization of speech perception and production in persons with Down Syndrome (DS) is still not clearly understood. The current study investigated the cerebral specialization for speech production using a mouth asymmetry paradigm. In right handed, non-handicapped subjects the mouth asymmetry methodology has shown a facilitation on the right side of the mouth during expressive speech. The right mouth asymmetry is believed to reflect the dominance of the left hemisphere for speech production (Graves, Goodglass & Landis, 1982). In the present study the lateralization for the production of speech was investigated in 10 right handed participants with Down syndrome and 10 non-handicapped subjects. The results indicated that a tendency for a right mouth advantage (RMA) at the initiation and end of speech production occurred in both subject groups. Surprisingly, the degree of asymmetry did not differ, suggesting that the focal representation of speech production is lateralized similarly in both subject groups. Additionally, a high proportion of verbal errors were made by individuals with DS. These results are consistent with the model of biological dissociation (Elliott & Weeks, 1993), which asserts that individuals with DS are impaired on verbal-motor tasks due to the functional separation between speech perception centers in the right cerebral hemisphere, and speech production centers in the left cerebral hemisphere.
Keywords: cerebral specialization; speech and complex oral verbal movement; down syndrome